2019
DOI: 10.21071/pbs.v0i7.11801
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate, heart rate variability and salivary cortisol as indicators of arousal and synchrony in clients with intellectual disability, horses and therapist during equine-assisted interventions

Abstract: The aim of the study was to analyse interaction processes in equine-assisted therapy (EAT) sessions with ten female clients in the period of emerging adulthood with intellectual disability (ID). Heart rate (HR), heart rate variability and salivary cortisol levels have been analysed in humans and horses before, during and after a standardised therapy session as well as in a control condition. There was a trend of lower cortisol levels and higher variability and parasympathetic tone induced by horses. During cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This study found that the intervention was associated with short-range functional connectivity in the regions of the brain related to the behavioural inhibition system, which are associated with symptom improvement. In addition, a recent pilot study [34] also reported on heart rate, heart rate variability, and salivary cortisol measurements in both humans and horses and reported reductions in cortisol for human participants post-intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that the intervention was associated with short-range functional connectivity in the regions of the brain related to the behavioural inhibition system, which are associated with symptom improvement. In addition, a recent pilot study [34] also reported on heart rate, heart rate variability, and salivary cortisol measurements in both humans and horses and reported reductions in cortisol for human participants post-intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In the HP ground phase, most of the physiological parameters decreased in the horses and in the patients, thus reflecting the relaxation of both (horses and patients) in the interaction phase on the ground, which seems to indicate a predominance of the parasympathetic NS, as has been suggested by other authors. Thus, other authors [ 30 ] studied the HR and the cortisol level in patients with intellectual disabilities and in the therapy horses. The parameters were measured at different moments of horse-patient interaction, observing a tendency to decrease both parameters in patients and horses during the cited interaction, which, according to the authors, reflects a decrease in stress by predominance of the parasympathetic NS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to attachment, behavioral synchrony (i.e., coordinated behaviors reflecting mutual attunement between interacting individuals [51]) is also rooted in the caregiver-infant bond. Although the findings by Pirrone et al did not reveal any synchronic patterns in the physiological reference markers heart rate or salivary cortisol [13], research in equine-assisted therapy has indicated that synchrony in heart rate varies with the relationship intensity in AAI recipients, horses and therapist [52]. Since cascading levels of stress may decrease synchrony between interacting individuals [53], it is an interesting phenomenon to study in the context of AAIs.…”
Section: Relationshipmentioning
confidence: 96%